Stillbirth in rural Bangladesh: arsenic exposure and other etiological factors: a report from Gonoshasthaya Kendra - Nicola Cherry; Kashem Shaikh; Corbett McDonald; Zafrullah Chowdhury
OBJECTIVE: To use data collected by Gonoshasthaya Kendra, a large nongovernmental organization providing health care to some 600 villages, to describe the epidemiological pattern of stillbirth and any additional contribution made by arsenic contamination of hand-pump wells in Bangladesh. METHODS: Completed pregnancies and outcomes (n = 30 984) for two calendar years, together with existing data on 26 socioeconomic and health factors were selected for study. The health care in these villages was administered from 16 geographical centres; information on the average arsenic concentration in each centre was obtained from the National Hydrochemical Survey. After univariate analysis, a multivariate, multilevel, logistic model for stillbirth was developed. The additional effect of arsenic was calculated having adjusted for all potential confounders thus identified. FINDINGS: The overall stillbirth rate was 3.4% (1056/30 984) and increased with estimated arsenic concentration (2.96% at < 10 Âµg/l; 3.79% at 10 Âµg/l to < 50 Âµg/l; 4.43% at > 50 Âµg/l). Having adjusted for 17 socioeconomic and health factors, the odds ratios estimated for arsenic (with < 10 Âµg/l as reference) remained raised: 1.23 (95% confidence interval, CI: 0.87Â-1.74) at 10 Âµg/l to < 50 Âµg/l and 1.80 (95% CI: 1.14Â-2.86) at 50 Âµg/l or greater. CONCLUSION: A increased risk of stillbirth is associated with arsenic contamination. This risk, substantial enough to be detected by an ecological approach and not readily attributable to unmeasured confounding, is essentially preventable and all efforts must be made to protect women at high risk.